2018
DOI: 10.28991/cej-0309167
|View full text |Cite
|
Sign up to set email alerts
|

Response of Skirted Foundations Resting on Dry Medium Dense Sand

Abstract: Experimental model tests were carried out to study the response of skirted foundation resting on dry sand.  The experiments were performed in a large soil container (1000  1000 mm in cross section and 800 mm in height).  Skirts with three different lengths (L) varied from 0.5D to 1.5D was attached to the edge of shallow circular foundations having three different diameters (D=60, 90 and 120 mm). Different parameters have been studied; these parameters involve skirt length, foundation size and skirt conditions.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 9 publications
0
2
0
Order By: Relevance
“…(Dawarci et al, 2014) presented the experimental research of a multi-edges footing resting on a sandy soil without structural skirts. (Haider & Mekkiyah, 2018) reported consequences based on a lab study of the monotonic loading response of the skirted shallow foundations on sand with different skirt depth 0.5D to 1.5D and different circular diameters. The results showed that the bearing capacity of foundation increases with increase depth skirted as well as diameter of foundation.…”
Section: Fig 2 Failure Mechanism Of Bearing Capacity With Skirted Fou...mentioning
confidence: 99%
“…(Dawarci et al, 2014) presented the experimental research of a multi-edges footing resting on a sandy soil without structural skirts. (Haider & Mekkiyah, 2018) reported consequences based on a lab study of the monotonic loading response of the skirted shallow foundations on sand with different skirt depth 0.5D to 1.5D and different circular diameters. The results showed that the bearing capacity of foundation increases with increase depth skirted as well as diameter of foundation.…”
Section: Fig 2 Failure Mechanism Of Bearing Capacity With Skirted Fou...mentioning
confidence: 99%
“…Soil confinement technique is very active and it has been used by many researchers such as (Watson and Randolph, 1997); (Byrne et al, 2002); (Al-Aghbari and Mohamedzein, 2004); (EL Wakil,2013); (Tripathy, 2013); (Dawarci et al, 2014); (Al-Aghbari and Mohamedzein, 2018); (Haider and Mekkiyah, 2018), where studies have investigated the use of coiled foundation on the sand. Mahmood.et al (2019) The effect of gypsum soil confinement on bearing capacity is studied.…”
Section: Introductionmentioning
confidence: 99%